Physiological, biochemical and nutritional changes in soybean in response to application of steel slag - da Silva, Alessandra Vieira [UNESP]; Deus, Angélica Cristina Fernandes [UNESP]; de Souza, Mara Lúcia Cruz [UNESP]; Broetto, Fernando [UNESP]; Büll, Leonardo Theodoro [UNESP] (Southern Cross Publishing, 2021)
Steel slag is a powdery industrial residue that has CaO, MgO and SiO2 in its composition, which enables its use in agriculture for soil acidity correction. Most studies involving this residue have focused on understanding its effects on the soil, not always considering its action on the plant metabolism. Thus, the present study aimed to evaluate physiological, biochemical and nutritional changes in soybean plants due to application of lime and steel slag on the soil surface or by incorporation. The experiment was carried out in the field, with six soil acidity corrective materials: stainless steel slag, steel slag, ladle slag, wollastonite slag, dolomitic lime and calcined dolomite, plus a negative control, which did not receive correctives. Two application methods were adopted: soil surface application or incorporation. Sixty days after application, the soybean crop was established. Soybean response changed with the application method, since incorporation of corrective materials provided greater production of fresh and dry leaf mass and stem fresh mass, increased chlorophyll b and leaf K levels, and contributed to a greater number of plants per hectare and pods per plant, compared to surface application. Besides such benefits, there was no difference between the effect of application methods on soybean yield, indicating that both incorporation and surface application are efficient in increasing soybean grain yield. The correctives steel slag, wollastonite and calcined dolomite provided significant increases in soybean yield.
Keywords: Glycine max; Liming; Silicate; Slags; Soil acidity